Isolation and Characterization of Mycoplasma mycoides Subspecies capri from Milk of Natural Goat Mastitis Cases. (20th May 2013) - Kumar, Vijay; Rana, Rajneesh; Mehra, Somya; Rout, Pramod Kumar
Abstract : Association of Mycoplasma mycoides subspecies capri ( Mmc ) with natural goat mastitis has been studied earlier largely by detecting the Mmc DNA using molecular methods. However, report on detection of cultivable Mmc isolates from natural goat-mastitis milk is still very rare. In this study, Mmc was isolated from milk samples (n = 171 ) of goats with or without clinical signs of mastitis. Mmc isolates were further characterized by biochemical and species-specific PCR methods. Intra species strain variation was also studied by 16S amplified rDNA restriction analysis (16S ARDRA). The study recovered a total of 6 Mmc isolates (3.5%). Three types of intraspecies variants among the recovered Mmc isolates were found by 16S ARDRA. The study concluded that Mmc may be an etiological agent of mycoplasmal mastitis in Indian goat herds.